Herbal products for the prevention and management of 5-fluorouracil-induced oral mucositis: A systematic review of preclinical evidence - Pocut Astari; Dewi F. Suniarti; Erik Idrus (Narra Sains Indonesia, 2026)
Oral mucositis is a painful and dose-limiting complication of chemotherapy, particularly in patients receiving 5-fluorouracil (5-FU). Herbal products have attracted increasing interest as supportive care candidates because of their antioxidant, anti-inflammatory, anti-apoptotic, and cytoprotective properties. This systematic review aimed to synthesize preclinical evidence on the effects and mechanisms of herbal products in 5-FU-induced oral mucositis models. A literature search was conducted in PubMed, Scopus, EBSCO, ScienceDirect, and ProQuest for studies published up to March 2026, following PRISMA guidelines. Eligible studies were in vitro studies, or studies with a clearly described in vitro component, that evaluated herbal extracts, multi-herbal formulations, or naturally derived plant-based compounds in 5-FU-induced oral mucositis models. Study reliability was assessed using the ToxRTool. Seven studies were included, comprising three in vitro-only studies and four combined in vitro–in vivo experimental studies published between 2014 and 2025. The evaluated products included Daiokanzoto, Salvia miltiorrhiza, Onchung-eum, anthocyanins from Oryza sativa, FITOPROT, cannabidiol, and Camellia tea saponin. Across the included studies, herbal products were reported to improve cell viability, reduce reactive oxygen species production, suppress inflammatory mediators, inhibit apoptosis, and promote epithelial repair. The main mechanisms involved the modulation of nuclear factor kappa-light-chain-enhancer of activated B cells signaling, caspase-3 activation, the Nrf2/Keap1/ARE pathway, mitochondrial dysfunction, and ferroptosis-related markers. All included studies were classified as reliable without restrictions, with ToxRTool scores ranging from 16 to 18. In conclusion, preclinical evidence suggests that herbal products may have protective effects against 5-FU-induced oral mucositis through antioxidant, anti-inflammatory, and cytoprotective mechanisms. However, standardized in vivo studies and clinical trials are needed before their therapeutic use can be recommended.